1998
DOI: 10.1063/1.121130
|View full text |Cite
|
Sign up to set email alerts
|

Submicron selective organometallic vapor phase epitaxy growth using tunable deep UV excitation

Abstract: We report on selective area growth of AlGaAs from trimethylgallium, trimethylaluminum, and arsine by UV laser stimulated organometallic vapor phase epitaxy. Using a wavelength tunable pulsed laser system, we investigated the stimulation mechanism and wavelength dependence of the growth enhancement in the range from 235 to 255 nm. Adlayer photolysis constitutes the dominant stimulation mechanism at these wavelengths, since the observation of laser-induced, submicron periodic surface ripples restricts the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Wankerl and co-authors demonstrated selective area growth of Al x Ga 1−x As mesas from trimethylgallium (TMG), trimethylaluminum (TMA) and arsine gases at 500 °C using a tunable, frequency doubled dye laser [90]. They achieved a growth rate differential between dark and illuminated growth regions of 1:3.2, averaging a growth rate of 2.6 µm in the illuminated area over the first 15 min of growth.…”
Section: Molecular Decomposition and Increased Growth Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wankerl and co-authors demonstrated selective area growth of Al x Ga 1−x As mesas from trimethylgallium (TMG), trimethylaluminum (TMA) and arsine gases at 500 °C using a tunable, frequency doubled dye laser [90]. They achieved a growth rate differential between dark and illuminated growth regions of 1:3.2, averaging a growth rate of 2.6 µm in the illuminated area over the first 15 min of growth.…”
Section: Molecular Decomposition and Increased Growth Ratesmentioning
confidence: 99%
“…89 They achieved a growth rate differential between dark and illuminated growth regions of 1:3.2, averaging a growth rate of 2.6 μm in the illuminated area over the first 15 minutes of growth. The growth rate differential depended strongly on the excitation wavelength, with selectivity dropping to near zero abruptly at wavelengths above 250 nm.…”
Section: Molecular Decomposition and Increased Growth Ratesmentioning
confidence: 99%